Predictors of patient satisfaction to nursing service in government hospitals in eastern Visayas Philippines - Rheajane Aguilar Rosales , (International Journal of Advanced Nursing Studies, 2024)
This study assessed the patients’ satisfaction level on the nursing service in government hospitals within Eastern Visayas, Philippines and determined the predictors of patient’s satisfaction using Stepwise Multiple Regression Analysis. The researcher primarily employed a de-scriptive correlational research design. Further, a standardized questionnaire named Risser -Patient Satisfaction Scale was employed to 203 patient respondents. This study revealed that Patients have greater satisfaction level on the competencies or capabilities of nurses in their respective field. However, respondents were less satisfied on nurses’ attitude toward patients, and on how they communicate with them. Moreover, this study also revealed that age, ward assignment, and service type was found to be the predictors of patients’            satis-faction.